Indonesia's Regional Head Elections: Political Dynamics and Problems - Ade Andriani (Universitas Syiah Kuala, 2023)
Up to this point, Indonesian political machinery has experienced cyclical instability dating back to the Orde Lama and Reformasi. Perpolitikan semakin mendekati iklim yang lebih demokratis dalam konteks era reformasi ini. Despite this, Indonesia continues to experience a period of democratic transition. Pemilihan Umum Kepala Daerah (Pemilukada) is the primary tool used by democratic mechanisms to create kepemimpinan in a certain region. After several years in Rezim Orde Baru's environment, where he failed to provide the populace with the opportunity to express their own opinions, Pemilukada was steadfastly adopted as a democratic path in the process of choosing the new head of state. There will be a strong focus on national and local politics in Indonesia starting in the year 2024, known as Pemilu and Pemilukada, respectively. In this article, we will explain how political dynamics operate in the current political climate